Strain improvement of Trichoderma harzianum for enhanced biocontrol capacity: Strategies and prospects - Xiao, Ziyang; Zhao, Qinqin; Li, Wei; Gao, Liwei; Liu, Guodong (Frontiers in Microbiology, 2023)
In the control of plant diseases, biocontrol has the advantages of being efficient and safe for human health and the environment. The filamentous fungus Trichoderma harzianum and its closely related species can inhibit the growth of many phytopathogenic fungi, and have been developed as commercial biocontrol agents for decades. In this review, we summarize studies on T. harzianum species complex from the perspective of strain improvement. To elevate the biocontrol ability, the production of extracellular proteins and compounds with antimicrobial or plant immunity-eliciting activities need to be enhanced. In addition, resistance to various environmental stressors should be strengthened. Engineering the gene regulatory system has the potential to modulate a variety of biological processes related to biocontrol. With the rapidly developing technologies for fungal genetic engineering, T. harzianum strains with increased biocontrol activities are expected to be constructed to promote the sustainable development of agriculture.